Microfoundations of Organizational Paradox: The Problem Is How We Think about the Problem - Miron-Spektor, Ella; Ingram, Amy; Keller, Joshua; Smith, Wendy K.; Lewis, Marianne W. (Academy of Management Journal, 2018)
Competing tensions and demands pervade our work lives. Accumulating research examines organizational and leadership approaches to leveraging these tensions. But what about individuals within firms? Although early paradox theory built upon micro-level insights from psychology and philosophy to understand the nature and management of varied competing demands, corresponding empirical studies are rare, offering scarce insights into why some individuals thrive with tensions while others struggle. In response, we contribute to the microfoundations of organizational paradox with a theoretical model and robust measures that help unpack individuals’ varied approaches to tensions. Following rigorous scale development in Study 1, including samples from the U.S., UK, Israel, and China, we test our model in a large firm in the U.S. using quantitative and qualitative methods. We identify resource scarcity (i.e., limited time and funding) as a source of tensions. We also demonstrate that a paradox mindset—the extent to which one is accepting of and energized by tensions—can help individuals leverage them to improve in-role job performance and innovation. Our results highlight paradox mindset as a key to unlocking the potential of everyday tensions.